Pengaruh Gaya Kepemimpinan Transformasional terhadap Disiplin Kerja ASN Dinas Kependudukan dan Pencatatan Sipil Kota Palembang - Karimudin, Yos; Wardana, Dwi Febi; Hadjri, Muhammad Ichsan; -, Zunaidah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of the transformational leadership style on the work discipline of the state civil servants at the Department of Population and Civil Registration of the City of Palembang. The population in this study were ASN of the Department of Population and Civil Registration using saturated sampling so that the sample used was the entire population of ASN of the Department of Population and Civil Registration, totaling 70 respondents. The data obtained is primary data by distributing questionnaires. The analysis technique used is simple linear regression analysis. Based on the results of the hypothesis analysis (t test), it was concluded that the transformational leadership style had a positive and significant effect on the work discipline of the state civil servants at the Palembang City Population and Civil Registration Service. Keywords: Transformational Leadership, Work Discipline